Development of car tire rack - Mohd Nurul Akmal, Mohd Yusof (2007)
This project is about designing and fabricating the car tire rack to help people store tire, transporting load or items more efficiently. This project involves the process of designing the car tire rack by considering the shape and also the ergonomic factor for people to use. After the design has completed, it was transformed to its real product where the design is used for guideline. The material of this design is easy to gain it, because it only using rectangular hollow steel and round steel. The process involves in this project is using welding process, using screws and nuts or threaded fasteners, grinding, drilling and the others process. This project also to make sure the product is safety for the user indeed of publishing. This project is mainly about generating a new concept of car tire rack that would make to store tire, transferring and transporting load or items become easier and more efficient.